Engineering Prelithiation of Polyacrylic Acid Binder: A Universal Strategy to Boost Initial Coulombic Efficiency for High‐Areal‐Capacity Si‐Based Anodes. (30th July 2022) - Li, Zeheng; Tang, Weiting; Yang, Yajun; Lai, Guoyong; Lin, Zheng; Xiao, Huayan; Qiu, Juncheng; Wei, Xiujuan; Wu, Shuxing; Lin, Zhan
Abstract: The low initial Coulombic efficiency (ICE) and insufficient cycling lives of silicon (Si)‐based anodes seriously hinder their eventual introduction into next‐generation high‐energy‐density lithium–ion batteries (LIBs). Herein, an engineering prelithiation binder strategy based on polyacrylic acid (Lix PAA) is proposed for representative SiOx anodes. The ICEs and cycling lives of SiOx anodes are significantly improved by precisely controlling the lithiation degree of PAA binder. The ICE of the high‐loading (3.0 mg cm −2 ) SiOx electrode increases by 10.9% when the Li0.75 PAA binder replaces the PAA binder. Moreover, the working mechanism of the lithiation binder strategy to improve the electrochemical performances (especially for ICE) is systematically investigated, which is universally applied to other Si anodes such as Si nanoparticles and Si/graphite. This universal binder strategy and proposed working mechanism provide enlightenment on constructing high‐ICE, high‐energy‐density, and long‐life Si‐based anodes. Abstract : Herein, the Lix PAA binders with optimal lithiation degrees are proposed for high‐areal‐capacity Si‐based anodes with high ICE. The Lix PAA binders stabilize the electrode structure while accelerating the Li transport kinetics of the electrode. The suppression of binder side reactions and the provision of extra Li sources via lithiation are also beneficial to enhance the ICEs of Si‐based anodes.